PENGUATAN LITERASI DIGITAL DAN KOMPETENSI DIGITAL SEBAGAI DETERMINAN KINERJA GURU DI ERA TRANSFORMASI PENDIDIKAN - Arni Bara Pongdatu; Jemi Pabisangan Tahirs; Stefani Marina Palimbong (ITB AAS Indonesia Surakarta, 2026)
The rapid advancement of digital transformation in education requires teachers to possess adequate digital literacy and digital competence to improve their professional performance. This study aims to analyze the influence of digital literacy and digital competence on teachers' performance at SMAN 4 Toraja Utara. The research employed a quantitative approach using an explanatory survey design. The population consisted of 40 permanent teachers, all of whom were selected as respondents through a saturated sampling technique. Data were collected using structured questionnaires measured on a five-point Likert scale and analyzed using multiple linear regression. The findings indicate that digital literacy has a positive and significant effect on teachers' performance. Likewise, digital competence significantly improves teachers' performance. Simultaneously, digital literacy and digital competence have a positive and significant influence on teachers' performance, explaining 72.8% of the variance in teacher performance. These findings suggest that strengthening teachers' digital literacy and digital competence is essential to enhancing professional performance and supporting the successful implementation of educational transformation in the digital era. Therefore, schools should continuously provide digital capacity-building programs to improve teachers' readiness in integrating technology into teaching and learning activities. Keywords: digital literacy, digital competence, teacher performance, educational transformation, digital education